The ECB and the single European financial market: A proposal to repair half of a flawed design - Mario Tonveronachi (Levy Economics Institute of Bard College, 2014)
The flaws of the Maastrict Treaty are a frequent object of commentary but, as yet, Europe remains unable - or, perhaps more accurately, unwilling - to address these flaws. The European project will remain unfinished and the ability of the European Central Bank to implement effective monetary policies will continue to be hobbled. As Mario Tonveronachi observes in this public policy brief, Europe has a currency union, but this does not mean that Europe has achieved a single financial market, an essential element for a functioning union. He reminds us that a single European market requires pricing in relation to common risk-free assets rather than in relation to a collection of individual idiosyncratic sovereign rates. And financial operators must have access to the same risk-free assets for trading and liquidity operations. The euro provides neither of these functions, and thus, while there has been a measure of convergence, a single financial market, and the financial integration it represents, remains unachieved.
Keywords: 330